Thin films hydroxyethyl cellulose/silver nanoparticles (HEC/AGNP) for antibacterial studies - Nurul Atikah , Abdul Halim (2012)
Thin films of hydroxyethyl cellulose (HEC) containing silver nanoparticles were prepared and characterized. Silver nitrate (AgNO 3 ) aqueous solution was reduced by HEC by heating and this solution was used to form the thin film. HEC/AgNP solution and the thin films were characterized using SEM and UV-Vis spectroscopy. The silver nanoparticles showed absorbance peak at 439 nm. Different solutions of HEC/AgNP were prepared with different concentration of silver nitrate. The thin films were cross-linked by heating at different temperatures and the effect of heating the thin films on the antibacterial property was studied. The thin films were used to study the antimicrobial effect on E. coli and S. aureus. The thin films of HEC/AgNP showed strong antimicrobial activity. HEC being a biocompatible and water soluble polymer is a very good candidate for wound dressing material.